Some aspects of reliability prediction of chemical industry and hydrogen energy facilities (vessels, machinery and equipment) operated in emergency situations and extreme conditions; International Journal of Hydrogen Energy; Vol. 86 - Gusev A. L. Alexander; Gafarov A. M. Aydin; Suleymanov P. H. Panah; Habibov I. A. Ibrahim; Malikov R, Kh. Rauf; Hasanov Ya. H. Yashar; Levina A. I.; Mikheev P. Pavel; Ufa R. A. Ruslan Alexandrovich (2024, 2024)
Title screen